Development and Evaluation of the PIKIBAR Game: A Gamified Approach to Reducing Math Anxiety in University Students - Siskawati, Fury Styo; Zayyadi, Moh (Jurnal Pendidikan MIPA, 2025)
Math anxiety is not a simple thing that can be ignored because it has an impact on not maximizing the achievement of mathematics learning outcomes. Based on the condition, the PIKIBAR game was developed to reduce math anxiety in algebra learning. This research aims to describe the process and results of developing the PIKIBAR game to reduce mathematical anxiety among University students. This development research utilized the ADDIE model and pre-service mathematics students from Universitas Islam Jember as the research sample. Data collection methods included interviews, observations, questionnaires, tests, and documentation, as well as data analysis methods that utilize percentages. The research results indicate that the development of the PIKIBAR game progressed through the ADDIE stages, which encompass analysis, design, development, implementation, and evaluation. Several parts need revision, with a score of 3.03 out of a maximum score of 4. At the same time, the practicality is very high, namely at a value of 86.25%. In terms of its effectiveness, it is said to be effective in reducing mathematical anxiety, as evidenced by a lower percentage among students who use it, specifically 40%, compared to the group of students who do not use it, at 80%. Judging from the average score of the questionnaire results given before using the game and after using the game. This game was designed with simple language and gradually guided the user from the beginning, starting with an easy level, then progressing to a medium level, and concluding with a difficult level, all without the user realizing it directly. For further research, if you want to use the same application to develop test and non-test instruments, avoid using the short form model because differences in writing can affect the results. For mathematical anxiety, it should be considered for monitoring material because it has a significant impact on learning outcomes and achievement, especially in mathematics.   Keywords: PIKIBAR game, math anxiety, algebra.